2020
DOI: 10.1177/0268580920966829
|View full text |Cite
|
Sign up to set email alerts
|

The framing of 9/11 in American, French, and Dutch national newspapers (2001–2015): An inductive approach to studying events

Abstract: In this article, the authors employ work on events, framing, and social problems to develop an inductive approach to studying events. The article’s central premise is that tracing direct references made to events offers a fruitful strategy to investigate their framing cross-nationally and over time. The authors apply their approach to the case of 9/11 in American, French, and Dutch national newspapers (2001–2015). By combining word counting, topic modeling, and content analysis they examine the amount of atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…The framing of 9/11 in the American and Dutch public spheres offers such a case. In prior research, I have found that significantly different meanings were attached to this event in national newspapers from the two countries over the 2001–2015 period (van Dooremalen & Uitermark, 2020 ). An important part of this research consisted of a topic‐modeling investigation.…”
Section: Cases Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The framing of 9/11 in the American and Dutch public spheres offers such a case. In prior research, I have found that significantly different meanings were attached to this event in national newspapers from the two countries over the 2001–2015 period (van Dooremalen & Uitermark, 2020 ). An important part of this research consisted of a topic‐modeling investigation.…”
Section: Cases Data and Methodsmentioning
confidence: 99%
“…DiMaggio et al., 2013 ; Marshall, 2013 ). A significant number of codes concerned foreign issues such as the War in Afghanistan and the Iraq War, as well as domestic issues like safety, Muslim integration, or national politics (see van Dooremalen and Uitermark ( 2020 ) for a more extensive explanation of the entire analysis).…”
Section: Cases Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por exemplo,Dooremalen & Uitermark (2020) combinam o uso de contagem de palavras, modelagem de tópicos e análise de conteúdo para examinar a atenção dada aos atentados de 11 de setembro de 2001, os assuntos aos quais eles foram ligados e as implicações atribuídas ao acontecimento, a partir de um corpus formado por publicações de jornais nos Estados Unidos, na França e nos Países Baixos, entre 2001 e 2015. Para medir a atenção dada aos atentados, os autores contaram quantas vezes o evento aparecia nas publicações.…”
unclassified
“…As for the research design, to investigate whether place matters for the cross-border impacts of terrorist attacks, we analyse newspaper articles from four American newspapers to measure three forms of impact: the attention that the attacks received, the degree to which they were 'domesticated', and the implications that were inferred from them (Cf. van Dooremalen & Uitermark, 2020). In addition, to find out why place and distance matter, we conduct a thematic content analysis (Cf.…”
mentioning
confidence: 99%